Point of Sales (POS) System Design using Design Thinking Framework for Motorcycle Workshop - Billy Macarius Sidhunata; Michael Kenang Gabbatha; Nicolas Arya Nanda Susilo; Pedro Manuel Lamberto Buu Sada; Biafra Daffa Farabi; Samuel Piolo; Yerik Afrianto Singgalen (Journal of Information System and Informatics, 2023)
The challenge of MSME business is the change of transaction systems from conventional to digital processes to minimize human error. This research offers an idea to identify problems, classify digital innovation ideas, analyze needs, and design management information systems Point of Sales (POS) modules in CV. Renaldi Motor. The method used in designing the management information system of the POS module of the OmO Jaya Workshop application is design thinking. The stages in this research consist of empathizing, defining, ideating, prototyping, and testing. The results of this study show that the problem faced by Micro, Small, and Medium Enterprises (MSMEs) workshop businesses is the process of recording transactions that still use conventional methods. Through the digital innovation of the POS module management information system in the form of the OmO Jaya workshop application. Through the application, a CV. Renaldi Motor is expected to optimize the digital transaction recording system and improve business performance. Thus, the risk of business losses due to human error can be minimized. In addition, the Blackbox test results show that the test results in each process have been successful and as expected. This study concluded that the Point of Sales (POS) System can improve CV. Renaldi Motor's business performance through digitizing the sales transaction recording process.